Development, Prevention, and Detection of Pineapple Translucency: A Review - Chuanling Li; Mingwei Li; Miaolin Zhang; Linpan Chen; Qingsong Wu; Junjun He; Zhong Xue; Xiumei Zhang; Yanli Yao (Agronomy)
Pineapple is one of the most important crops in tropical and subtropical areas. However, its production has been seriously impacted by the issue of fruit translucency in the past several decades. Fruit translucency is a physiological disorder of pineapple flesh with water-soaked core which results in a decline in pineapple quality. It has become a significant challenge for the sustainability of pineapple industry. Currently, the cause and pathophysiological development of pineapple translucency still have not been fully understood. The preventative and remedial measurements on the disease have yet to be effectively implemented in the production process. This review provides comprehensive information and the latest research progress on the possible pathogenesis, initiating factors, preventive and control practices, and detection techniques for pineapple translucency. Furthermore, the progress of research on apple and pear fruit translucency in recent years is reviewed and compared with pineapple translucency. The review offers theoretical guidance and insightful knowledge for the investigation of pineapple translucency disease.